Gathering consumer terminology using focus groups: an example with beauty care - Sasse, Audra Megan (Kansas State University, 2018)
Using consumer-friendly terminology is important in order to design and conduct consumer research that is relevant and impactful. As an example, today’s marketing is starting to evolve more towards catering to emotional responses, and focus groups are an effective way to gather emotional and attitudinal information in ways that surveys and questionnaires cannot. The objective of this study was to use focus groups as a tool to generate rich information related to emotions, attitudes and other aspects associated with beauty care products in order to provide terminology that is more simple, relevant and impactful. This terminology can then be used to design studies that will better help during product development and product marketing. Women in the Kansas City area were recruited for three focus groups in one of three age groups: 18-35, 36-50, and 51+ (7 women in each group). They were asked questions regarding their thoughts and emotions behind their purchasing habits and use of beauty care products, both positive and negative. Their opinions on ingredients used were also obtained. The focus groups were very useful to obtain consumer generated terminology on emotions, benefits and ingredients. For example, women reported that when not using certain beauty care products, they felt tired, dirty and self-conscious, whereas when they did use certain beauty care products, they reported feeling confident, clean, and beautiful. They also mentioned the importance of ingredients. Women overwhelmingly wanted products to have a more natural ingredient base and to be created “cruelty-free” (tested without having ever been tested on animals). These qualitative techniques will help provide terms that are more relevant and meaningful to consumers, and with this, help marketers and researchers better understand the consumer, in this case, understand women’s feelings and emotions related to the use of beauty care products so companies can better communicate with their target users.
Keywords: Beauty care; Emotions; Terminology; Focus groups